(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
The first detailed study on chaetetids from the Buckhorn Asphalt Quarry Lagerstätte is presented. Among the investigated specimens we found two samples (chaetetid specimens 2 and 6) that are different from all others in the quarry. Thin sections of these display a complex fragmentation of these Buckhorn chaetetids. Additionally, one of these samples contains two chaetetid morphotypes growing side by side, thus, in the same paleoenvironment. These specimens differ in their mode of growth (laminar and domical), which suggests that chaetetid growth was most likely influenced by genetic factors rather than by the paleoenvironment. We observed a feature, not hitherto reported as far as we are aware, on the surface of chaetetids; namely a regular clustering of seven tubules surrounding a central tubule. This feature could have had an exhalant function. Mineralogical analyses of the skeleton indicate primary high magnesian-calcite mineralogy, which is in accordance with reports in the literature. Cements precipitated during diagenesis are either calcite or dolomite and, where associated with microbial mats, they may contain a distinct amount of manganese. The comparison of the chaetetid skeletons from the Buckhorn Asphalt Quarry leads to the impression, that they represent various morphotypes or even species. Because of the lack of unique features, we have refrained however, from describing new species.